SCRUB FROM ORANGE PEEL AND WATERMELON TO SOFTEN AND BRIGHTEN THE SKIN - Ataya, Muhammad Fariq; Irawan, Muhammad Albizar Agyfahmi; Naufal, Rakha Zuhdi; Ramadhan, Rifan Arkana; Praza, Alvin Rediaska; Hidayat, Andri Syarif (Cendikia: Jurnal Pendidikan dan Pengajaran, 2025)
The study explores the innovative utilization of fruit peel waste, specifically orange and watermelon peels, as key ingredients in the formulation of a natural body scrub. These peels are rich in Vitamin C, antioxidants, and natural acids, contributing to skin health and beauty. The research involved collecting, drying, and grinding the peels, followed by blending them with natural binders and essential oils to create the body scrub. The product was evaluated through physical property assessments, pH testing, antioxidant activity assays, and user trials. Results indicated that the scrub effectively exfoliated the skin, improved texture and hydration, and was well-tolerated by users. This study highlights the potential of repurposing organic waste for sustainable skincare solutions, offering an eco-friendly alternative to conventional products. The findings suggest that this fruit peel-based body scrub could be further developed for commercial use, promoting both skin health and environmental sustainability